Understanding confusion in Africa : the politics of multiculturalism and nation-building in Cameroon - Fossungu, Peter Ateh-Afac (Langaa RPCIG ; Distributed in and outside N. America by African Books Collective, 2013)
Cameroon is considered to be Africa's legendary pathfinder. This book argues essentially that Cameroon cannot competently champion African unity and progress until it can correctly pursue its own multicultural nation-building. Cameroon's success continental-wise would depend on its theory and practice of multiculturalism, as particularly reflected in (1) the rejoicing in its historical diversity and the harmonious co-existence of its Systems of Education which must, of necessity, be linked to (2) effective federalization or decentralization of uniquely cultural matters. Critically examining history and education as components of culture, and therefore, of multiculturalism, the book makes bold recommendations while demonstrating how nation-building is meaningless without the people's authentic history.